A226 PERCEPTION OF PPI PRESCRIBING AMONGST RESIDENTS AND FELLOWS TRAINING IN PRIMARY AND SPECIALTY CARE. (1st March 2018) - Taheri Tanjani, M; Al Khoury, A; Hari, B; Martel, M; Barkun, A N
Abstract: Background: Proton pump inhibitors (PPI) are widely prescribed in North America. Several adverse events linked to their use, most probably not causal, have been reported. Yet no prescribing guidelines have addressed how to balance PPI efficacy in light of such possible side effects. Aims: To acquire knowledge on the varying perceptions of outpatient PPI long-term prescribing (≥8 wks) amongst primary and specialty care residents/fellows in 2 Canadian Universities. Methods: A web-based survey was completed by Family Medicine (FM), Internal Medicine (IM), and Gastroenterology (GI) residents/fellows. A knowledge assessment component examined the participants' understanding of pertinent efficacy data in the literature and approved indications, as well as literature on PPI-related possible side effects. 20 case scenarios with related targeted management questions were created. Demographics are expressed as proportions; inferential testing compared prescribing decisions between juniors (PGY1/2 FM and 1/2/3 IM) vs senior trainees, and across specialties. Results: Between April and July 2017, 163 trainees participated in the survey (FM 51%, IM 44%, and GI 5%). 83% were junior trainees, 17% senior, 59% female; 53% practicing in Ontario, 85% were aged 26–35 yrs. Only 42% had received formal education on prescribing long-term PPI, while 93% believed they would benefit from such teaching. 98% would follow detailed prescribing guidelines. No between-group differences were observed in the appropriate identification of recommended indications, nor of presumed associated side-effects when comparing juniors to seniors, or different specialties. Significant differences were noted in deprescribing PPIs appropriately or inappropriately given established indications in the presence of possible side-effects. 13 clinical stems described an absolute indication for long-term PPI use that should have overshadowed concerns about various possible PPI side effects. Inappropriate discontinuation of the PPI was suggested by 26%-76% of respondents. Amongst 7 clinical stems that described a poor indication for long-term PPI use, despite the introduction of various possible PPI side effects, respondents still elected to continue PPIs inappropriately in 15–44%. Proportions of possible inappropriate prescribing were significantly different according to training seniority in 4 of 20 scenarios, and differed by specialty in 7. Conclusions: There exist significant differences in prescribing attitudes according to level of training and in primary care versus specialty programs, leading to varying levels of inappropriate PPI de/prescribing practices. These findings highlight the need for the creation and wide diffusion of multidisciplinary guidelines to better assist young practitioners in learning optimal management strategies for patients being considered for long-term PPI use Funding Agencies: CAG